1996
DOI: 10.1084/jem.183.4.1899
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitogen-activated protein kinases with microtubules in mouse macrophages.

Abstract: SummaryTaxol, a microtubule-binding diterpene, mimics many effects of lipopolysaccharide (LPS) on mouse macrophages. The LPS-mimetic effects of taxol appear to be under the same genetic control as responses to LPS itself. Thus we have postulated a role for microtubule-associated proteins (MAP) in the response of macrophages to LPS. Stimulation of macrophages by LPS quickly induces the activation of mitogen-activated protein kinases (MAPK). MAPK are generally considered cytosolic enzymes. Herein we report that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…These results are consistent with reports that microtubule anomalies cause a net increase in tyrosine phosphorylation (Bershadsky et al, 1996, Wolfson et al, 1997, but decreases also have been reported (Roberge et al, 1993). More recently, microtubule perturbations have been shown to activate the mitogen-activated protein kinase (MAPK) (Extracellular signal-regulated kinase, ERK) pathway (Ding et al, 1996, Yujiri et al, 1999, which suggests a possible mechanism for microtubule-associated apoptosis in non-neuronal cells. A panERK antibody (Transduction Laboratories), however, failed to Figure 4B and D).…”
Section: Tyrosine Phosphorylation Of a 90 Kda Proteinsupporting
confidence: 88%
“…These results are consistent with reports that microtubule anomalies cause a net increase in tyrosine phosphorylation (Bershadsky et al, 1996, Wolfson et al, 1997, but decreases also have been reported (Roberge et al, 1993). More recently, microtubule perturbations have been shown to activate the mitogen-activated protein kinase (MAPK) (Extracellular signal-regulated kinase, ERK) pathway (Ding et al, 1996, Yujiri et al, 1999, which suggests a possible mechanism for microtubule-associated apoptosis in non-neuronal cells. A panERK antibody (Transduction Laboratories), however, failed to Figure 4B and D).…”
Section: Tyrosine Phosphorylation Of a 90 Kda Proteinsupporting
confidence: 88%
“…56,57 Microtubules are associated with serine/threonine kinases and phosphatases. [58][59][60][61] As the plasma membrane is an important source of signals during interphase, microtubules may be a principal location of signaling following mitotic arrest. Since mitochondria, an organelle where many members of the Bcl-2 family reside, 62 has proximity to microtubules, this may direct microtubule disruption to the apoptotic machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule damaging agents have been shown to activate MAPK without altering the level of MAPK expression (Ding et al, 1996;Wang et al, 1998;Shtil et al, 1999). We therefore investigated the effects of ATRA and docetaxel on MAPK activity.…”
Section: Effect Of Atra and Docetaxel On Activation Of Mapkmentioning
confidence: 99%